2023
DOI: 10.1186/s12909-023-04065-y
|View full text |Cite
|
Sign up to set email alerts
|

Allied health workforce development for participant-led services: structures for student placements in the National Disability Insurance Scheme

Abstract: Background Health, disability, and community services are increasingly transitioning from government-led to participant-led funding models, which intend to increase choice and control for service users. Allied health practitioners, who provide many frontline services within the resultant marketised environment, must adjust their knowledge and skills to meet participants’ expectations. However, future workforce strategies to address allied health student capabilities to provide these services ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
1
0
1
Order By: Relevance
“…Este estudio examinó los entendimientos y prácticas cambiantes relacionados con la colocación de estudiantes de atención médica durante la implementación de un modelo de financiación dirigido por participantes en el sector de discapacidad de Australia: el Plan Nacional de Seguro de Discapacidad. (Attrill et al, 2023) Síntesis de la cuarta fase de actividad comunal especializada Aplicar servicios…”
Section: Etapas Etapa 10 Diseño Urbano Y La Planificación Espacialunclassified
“…Este estudio examinó los entendimientos y prácticas cambiantes relacionados con la colocación de estudiantes de atención médica durante la implementación de un modelo de financiación dirigido por participantes en el sector de discapacidad de Australia: el Plan Nacional de Seguro de Discapacidad. (Attrill et al, 2023) Síntesis de la cuarta fase de actividad comunal especializada Aplicar servicios…”
Section: Etapas Etapa 10 Diseño Urbano Y La Planificación Espacialunclassified
“…Healthcare professionals have reported that ongoing education and training opportunities have improved their knowledge and procedural skills in client (e.g., patients, residents in aged care homes) care [ 28 ]. Since the COVID-19 pandemic, access to online professional development modules and training has improved [ 29 ]. However, a lingering question persists: can the co-creation of training programs and educational modules effectively contribute to the knowledge and skills development of both allied health students and healthcare staff?…”
Section: Introductionmentioning
confidence: 99%